EFFECT OF RANIBIZUMAB AND AFLIBERCEPT ON RETINAL PIGMENT EPITHELIAL DETACHEMENT, SUBRETINAL AND INTRARETINAL FLUID IN AGE-RELATED MACULAR DEGENERATION - Sumarová, P; Ovesná, P; Matušková, V; Beránek, J; Michalec, M; Michalcová, L; Autrata, D; Vysloužilová, D; Chrapek, O (Ceska a slovenska oftalmologie, 2022)
PURPOSE: The aim of the study was to compare the effect of three initial doses of the anti-VEGF ranibizumab and aflibercept medication on serous pigment epithelial detachment (PED), subretinal fluid (SRF) and intraretinal fluid (IRF) in the macula of treatment naive neovascular AMD (nvAMD) patients. MATERIAL AND METHODS: The cohort consists of 148 patients, of which 74 patients were treated with ranibizumab (51 females and 23 males) and 74 with aflibercept (46 females and 28 males). The data was recorded prospectively from the moment of diagnosis and start of treatment for a period of 3 months. At the moment of diagnosis and 3 months later, an OCT examination (Spectralis OCT, Heidelberg Engineering, Heidelberg, Germany) was performed. The OCT examination included a macular scan with 25 scans. Using the OCT instrument software, we measured the maximum anterior-posterior elevation of serous PED, the highest thickness of SRF and the largest diameter of the intraretinal cystic space. The statistical significance of differences between groups was evaluated using the t-test for continuous data and the Fisher exact test for categorical data. Changes in values of continuous variables over time were evaluated using the Wilcoxon paired test. Paired comparisons of binary parameters were determined by the McNemar test. RESULTS: Full regression of PED, SRF and IRF occurred in 3 (4.1%), 25 (39%) and 20 (51%) patients treated with ranibizumab, and in 5 (7.9%, p = 0.470), 28 (47%, p = 0.470) and 25 (57%, p = 0.827) patients treated with aflibercept, respectively. The average regression of PED, SRF and IRF was -60.4 μm (median -37.5 μm), -84.3 μm (median -85 μm) and -109.3 μm (median -81 μm) in patients treated with ranibizumab, and -46.3 μm (median -30 μm, p = 0.389), -127.7 μm (median -104 μm, p = 0.096) and -204.4 μm (median -163 μm, p = 0.005) in patients treated with aflibercept, respectively. We did not show a statistically significant difference in the regression rates of PED, SRF and IRF between the ranibizumab and aflibercept groups. (in patients with IRF after adjustment of the higher baseline IRF volumes in patients treated with aflibercept, p = 0.891). CONCLUSION: We are convinced that ranibizumab and aflibercept have the same effect on serous PED, SRF and IRF in the macula in patients with treatment naive nvAMD during the initial loading phase.
Keywords: Intravitreal Injections; Vascular Endothelial Growth Factor A; Retinal Detachment; inhibitory angiogeneze; vlhká makulární degenerace; Ranibizumab; ranibizumab; Humans; receptory vaskulárního endoteliálního růstového faktoru; Recombinant Fusion Proteins; subretinal fluid; Female; optická koherentní tomografie; odchlípení sítnice; lidé; Wet Macular Degeneration; intraretinal fluid; retinální pigmenty; Receptors, Vascular Endothelial Growth Factor; ženské pohlaví; injekce intravitreální; aflibercept; Male; vaskulární endoteliální růstový faktor A; Retrospective Studies; age related macular degeneration; Angiogenesis Inhibitors; pigment epithelium detachment; rekombinantní fúzní proteiny; age-related macular degeneration; retrospektivní studie; Tomography, Optical Coherence; Retinal Pigments; mužské pohlaví; Visual Acuity; zraková ostrost